2016
DOI: 10.1063/1.4967277
|View full text |Cite
|
Sign up to set email alerts
|

Effects of background gas on sulfur hexafluoride removal by atmospheric dielectric barrier discharge plasma

Abstract: The effects of background gases (He, Ar, N2 and air) on SF6 removal in a dielectric barrier reactor were investigated at atmospheric pressure. A comparison among these background gases was performed in terms of discharge voltage, discharge power, mean electron energy, electron density, removal efficiency and energy yield for the destruction of SF6. Results showed that the discharge voltage of He and Ar was lower than that of N2 and air, but the difference of their discharge power was small. Compared with three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 22 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…There may be also differences in electron density, temperature, and energy as well as in UV light intensity, but these are supposed to be small as compared to O radicals. 8 Comparative tests in this study were conducted at a fixed voltage. Discharge power determined from VQ Lissajous figures for different atmospheres was 35.6 W for argon, 26.0 W for air, and 16.5 W for oxygen; sterilization effect was the highest in oxygen rich in O radicals even when applied voltage was increased to reach same discharge power as in argon or in air.…”
Section: Discussionmentioning
confidence: 99%
“…There may be also differences in electron density, temperature, and energy as well as in UV light intensity, but these are supposed to be small as compared to O radicals. 8 Comparative tests in this study were conducted at a fixed voltage. Discharge power determined from VQ Lissajous figures for different atmospheres was 35.6 W for argon, 26.0 W for air, and 16.5 W for oxygen; sterilization effect was the highest in oxygen rich in O radicals even when applied voltage was increased to reach same discharge power as in argon or in air.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the active particles of Ar were all Ar I-type lines, which were generated when the excited state of Ar atoms transited to a lower energy level. The Ar gas ratio accounted for 98%, and Ar easily obtained the energy required to generate excited state particles [46], therefore in all three systems, the Ar lines were the strongest lines. There were also S and F lines in the three spectra.…”
Section: Products Analysismentioning
confidence: 94%
“…The experimental setup has been described in our previous study [12] and is shown in Figure 1. In this experiment, the discharge frequency is maintained at 8.5-9.0 kHz and input power is controlled within 100 W. We selected argon (Ar) as the background gas for SF 6 dilution due to its promotion effects on the discharge and SF 6 degradation [21]. The standard gases of Ar and SF 6 are in high purity of 99.99%, and they are mixed to a certain proportion by a gas sample compounder.…”
Section: Experimental Setup and Degradation Parametersmentioning
confidence: 99%